Outcome of fragility hip fractures in elderly patients: Does diabetes mellitus and its severity matter?. (March 2021) - Frenkel Rutenberg, Tal; Vintenberg, Maria; Khamudis, Alexander; Rubin, Tomer; Rutenberg, Ran; Bdeir, Abdelazeez; Shemesh, Shai
Highlights: Diabetes mellitus and osteoporosis are both diseases of epidemic proportions. Fragility hip fractures (FHF) are associated with elevated morbidity and mortality. The diabetes complications severity index predicts increased mortality following FHF. Cerebrovascular events were nearly 5 times more prevalent in diabetic FHF patients. Diabetic patients require specialized care during the peri-operative period of FHFs. Abstract: Aims: Diabetes mellitus (DM) and osteoporosis are both diseases of epidemic proportions with an increasing incidence worldwide. Fragility hip fractures (FHF) are associated with elevated morbidity, mortality, social burden and medical costs. The aim of this study was to determine whether patients with DM have worse medical and surgical outcomes following FHFs and whether the Diabetes Complications Severity Index (DCSI) can predict in-hospital complications and one-year mortality. Methods: A single centre retrospective cohort study including 1343 patients older than 65 years who underwent surgery for FHFs was conducted. The data collected included length of hospital stay, time-to-surgery, blood loss, complications and mortality during the first post-operative year. Results: 408 patients with a DM diagnosis were compared with 935 without DM. Pre-operatively, patients with DM had lower haemoglobin levels, higher platelet counts and worse renal function. Following surgery, patients with DM were more likely to be transferred to another department or intensive care. One-year mortality was significantly higher in the DM group [23.3% vs. 17.1%, odds ratio 1.36 (CI 1.029–1.799, p  = 0.03)]. Higher DCSI scores were related with elevated one-year mortality rates in the DM group. Cerebrovascular events were found to be nearly five times more prevalent in the DM group. Patients with DM were more likely to continue treatment in a rehabilitation centre and had a higher probability to be re-hospitalized in the first post-operative year (p.<0.001). Conclusions: Our results emphasize the increased vulnerability of this patient population and the importance of specialized care during the peri-operative period of FHFs.